THE FEMALE FACE OF UKRAINIAN DIPLOMACY IN THE UPR ERA - Holovko, Svitlana; Holovko, Nataliia (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
Purpose: to study the role of Ukrainian women in the formation of the diplomatic service of the UPR era in the context of the development of modern diplomacy. Research methods: based on the results of comparative legal analysis, the peculiarities of the implementation of the gender approach in the development of modern diplomatic service; methods of historical and chronological and historical reconstruction are used to recreate the role of women in the formation of the Ukrainian diplomatic service of the UPR era; the prognostic method is used as a tool for determining the prospects for further development of the principle of gender equality in domestic diplomacy and justifying its importance for improving the effectiveness of diplomatic service. Results: the problem of observance of the gender principle in the activities of the modern diplomatic service of Ukraine, ensuring the conditions for its full implementation and outlining its historical and legal origins is actualized; the positive influence of Ukrainian women on the process of formation of the national diplomatic service of the Ukrainian People’s Republic, the development of foreign policy relations and its positioning in the world as an independent sovereign state is substantiated; the historiographical analysis of individual personalities and the achievements of Ukrainian diplomats of the specified period are carried out; the historical origins of the national traditions of observance of the principle of gender equality in the organization of the diplomatic service are substantiated and the prospects for its further development in the context of Ukraine’s European progress are determined. Discussion: the historical role of women in the development of the Ukrainian diplomatic service as a condition for the implementation of a gender approach in modern conditions.